Macsyma - Macsyma Inc. ([Arlington, MA] Macsyma Inc., 1982)
A symbolic-numerical-graphical mathematics software product that can be used to solve simple or complicated computations in algebra, trigonometry, calculus, numerical analysis and graphics.
System requirements: IBM PC or compatible with at least a 80386 processor and a 387 math coprocessor; 8MB RAM; MS-DOS 5.0, PC DOS 6.0 or 6.1, DR-DOS 6.0, Novell DOS 7; MS-Windows 3.1 or MS-Windows for Workgroups 3.11; 17 MB hard disk space.
Keywords: Mathematics -- Software